Students’ parental socio-economic status, parenting styles and academic performance of secondary school students in ojo local government area, Lagos State - Etobro, Akpezi Benjamin; Odebowale, Ireti Tina; Olagunju, Isioma (Universitas Negeri Padang, 2022)
The home is the first point of contact of an individual’s learning. Some societal factors such as lack or inefficiency of safety, residential location and poverty alienation policies have conferred a sense of inequality among the citizenry. This study is focused on the efficacy of parental socio-economic status, parenting styles and academic performance of secondary school students in Ojo Local Government Area, Lagos State. Three research questions guided the study. The researcher adopted a descriptive survey research. A self-developed research instrument with a reliability index of 0.85 was used to collect data. Findings showed that there was no significant difference in the academic performance of secondary school students in Biology on the basis of their parenting styles, F(3, 448) = 2.552; p = 0.055. Also, there was significant composite contribution of parental socio-economic status and parenting styles on the students’ academic performance (F(2, 449) = 67.194; p < 0.05).